Single-tier City Logistics Model for Multi Products - Nova Saragih; Senator Nur Bahagia; Suprayogi Suprayogi; Ibnu Syabri (International Journal of Supply Chain Management, 2018)
Single-tier city logistics system consists of three entities which are suppliers, UCCs (urban consolidation centers), and retailers. This paper develops a model for single-tier city logistics system with multi products that has never been developed before. This paper also considers traffic congestion in the model so it more represents the real system in a city. Demands of the products follow a normal distribution. The problems that will be answered in this paper are how to determine the location of suppliers, to allocate retailers to opened UCCs, to assign suppliers to opened UCCs, to control inventory in the three entities involved, and to determine the route of the vehicles from opened UCCs to retailers. All the decisions will be simultaneously optimized. The model is solved using LINGO 12. Three numerical examples with different values of parameters are conducted to test the proposed model. All numerical examples show that the proposed model results logical solution.